Subsurface energy footprints - Grant Ferguson (Environmental Research Letters, 2013)
Anthropogenic climate change and energy security concerns have created a demand for new ways of meeting society’s demand for energy. The Earth’s crust is being targeted in a variety of energy developments to either extract energy or facilitate the use of other energy resources by sequestering emitted carbon dioxide. Unconventional fossil fuel developments are already being pursued in great numbers, and large scale carbon capture and sequestration and geothermal energy projects have been proposed. In many cases, these developments compete for the same subsurface environments and they are not necessarily compatible with each other. Policy to regulate the interplay between these developments is poorly developed. Here, the subsurface footprints necessary to produce a unit of energy from different developments are estimated to assist with subsurface planning. The compatibility and order of development is also examined to aid policy development. Estimated subsurface energy footprints indicate that carbon capture and sequestration and geothermal energy developments are better choices than unconventional gas to supply clean energy.